THE ROLE OF TERMINOLOGY IN LEXICOLOGY - Abduvoitov Ravshanbek Alijonovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Terminology is not just a technical or specific example of common language. In today's society, which values science and technology, the way expert knowledge concepts are named, structured, described and translated has given the term or naming of knowledge concepts. Get the expert up on stage. Information in scientific and technical texts is encoded in specialized terms or knowledge units, which are points of access to more complex knowledge structures. Beneath the information contained in the text are entire conceptual domains, explicitly and implicitly presented, and representing codified expertise.